Sistem Pengecekan Status Dokumen Jemaah Umroh Pada PT. Solusi Balad Lumampah Cabang Jakarta Berbasis Web - Rizky S., Octa; Ziveria, Mira (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
Currently many Muslims are traveling to perform the pilgrimage and umroh. It is also supported by one of the religious obligations of Islam that ordered the followers to perform the pilgrimage and umrah for the capable. But to be able to travel hajj or umroh is required for to have some supporting documents. Related documents supporting the pilgrims and umroh journey if prospective pilgrims have lack of supporting documents, the administration of PT. Balad Lumampah solution will contact prospective congregation by phone or SMS which is considered very inefficient. The purpose of this research is to build a system of checking the status of pilgrim document by using website at PT. Balad Lumampah Solution. The method used for system development is Prototyping and built with PHP programming language. The result of this system is facilitate prospective congregation in knowing the development of supporting documents being processed.